Demand Analysis of Informational Shipboard Gun Weapon System Interface Design - WANG Hui-chuan; ZHAO Xiao-zhe (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
According to development demand of informational shipboard gun weapon system, design concept of shipboard gun weapon system interface is proposed. System composition is put forward and function demand of interface is analyzed from combat, training and detection aspects. General principle need to be followed in design process. A new concept is provided for development of shipboard gun weapon system interface. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2395